2017
DOI: 10.1186/s12913-017-2561-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer drug funding decisions in Scotland: impact of new end-of-life, orphan and ultra-orphan processes

Abstract: BackgroundThe Scottish Medicines Consortium evaluates new drugs for use in the National Health Service in Scotland. Reforms in 2014 to their evaluation process aimed to increase patient access to new drugs for end-of-life or rare conditions; the changes include additional steps in the process to gain further information from patients and clinicians, and for revised commercial agreements. This study examines the extent of any impact of the reforms on funding decisions.MethodData on the Scottish Medicines Consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Reorganization, grouping, and renaming of registries is common. Other 33 , (76-84) 34,35,36,37,38,39,40,41,42,43,44,45,46,47 , (67, 85, 86) 1,48 , (87) 2,3 , (88, 89) 4,5 , (90, 91) 6,7,8,9 , (92,93).…”
Section: Disease Registries National Plans For Rare Diseasesmentioning
confidence: 99%
“…Reorganization, grouping, and renaming of registries is common. Other 33 , (76-84) 34,35,36,37,38,39,40,41,42,43,44,45,46,47 , (67, 85, 86) 1,48 , (87) 2,3 , (88, 89) 4,5 , (90, 91) 6,7,8,9 , (92,93).…”
Section: Disease Registries National Plans For Rare Diseasesmentioning
confidence: 99%
“…In Scotland, a series of reforms were instigated in 2014, which were designed to increase patient access to new drugs for orphan diseases, such as some types of GEP-NETs, as well as drugs used for end of life care (defined as a disease stage where death usually occurs within 3 years) [ 38 ]. The SMC have also previously reported that higher ICERs and/or greater uncertainty may be accepted for new treatments for orphan diseases or for agents that confer a considerable improvement in life expectancy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The value‐based pricing initiative of 2010 proposed additional weighting factors for decision‐making and included severity and carer impact . The SMC's Patient and Clinician Engagement process provides a mechanism to identify additional aspects of value, and themes discussed have included hope, independence, and toxicity . A recent independent review of SMC funding decisions proposed development of a “basket” of measures, to include wider societal benefits .…”
Section: Discussionmentioning
confidence: 99%
“…38 The SMC's Patient and Clinician Engagement process provides a mechanism to identify additional aspects of value, 17 and themes discussed have included hope, independence, and toxicity. 39 A recent independent review of SMC funding decisions proposed development of a "basket" of measures, to include wider societal benefits. 40 Our findings may also point to aspects of health care that matter to the public beyond health maximization.…”
Section: Discussionmentioning
confidence: 99%